Automatic Monitoring System in Fodder System for Livestock - Che Amran, Muhammad Faris Ridhwan; Mohamad Hairol Jabbar (Evolution in Electrical and Electronic Engineering, 2022)
The fodder system can provide food for a wide range of livestock used for milk and meat production. Hydroponically grown green fodder is made from forage grains that are germinated and grown for a short period inside special growing rooms with the proper growing conditions. However, a food shortage is happening because farmers are dependent on feeding their livestock with maize pellets. Some of them are trying to use green fodder, which requires them to harvest it weekly. Therefore, this project will be designed to monitor humidity and temperature to create a suitable environment for green maize fodder. The project starts by collecting materials reading, specifically the temperature and humidity of the surrounding environment. A water level sensor indicates the low amount of water in the tank. The average daily temperature in Malaysia is 21 to 32ºC and the relative humidity is 80.5%. So, if the reading of the temperature and humidity sensors is not in the range needed, then the water pump and cooling fan will turn on and vice versa. The sensors are expected to send data to the Raspberry Pi, which reads it and switches on the actuators when they receive a signal from the sensor or actuator as needed for temperature and humidity monitoring.